Fast Dissolving Sublingual Films Containing Sumatriptan Alone and Combined with Methoclopramide: Evaluation in Vitro Drug Release and Mucosal Permeation - Maryam Maghsoodi, Mahdieh Rahmani, Hamed Ghavimi, Seyed Hassan Montazam, Saieede Soltani, Mitra Alami, Sara Salatin, Mitra Jelvehgari (Tabriz University of Medical Sciences, 2016)
ackground: Sumatriptan succinate is a 5-HT1 receptor agonist which is used in the treatment of migraine. It shows low bioavailability (15%) due to high hepatic first pass metabolism. The present work intended to formulate mucoadhesive sublingual films of sumatriptan combined with metoclopramide and sumatriptan alone with the objective of improving the therapeutic efficacy, patient compliance, and bioavailability. Methods: The sublingual films were formulated by solvent casting technique using mucoadhesive polymer of hydroxypropyl methylcellulose and propylene glycol as plasticizers. This study was also designed to evaluate the physicochemical and mucoadhesive characteristics of the films. The films were evaluated for their mechanical strength, folding endurance, drug content uniformity, swelling, in vitro residence time, in vitro release, in vitro bioadhesion, and in vivo mucoadhesion. Results: They showed good appearance and elasticity. The best drugs of polymer ratio were S3 (1:2) and SM2 (2.7:1:8). The film of S3 and SM2 showed 10.6 and 11.01 mg weight, 2.2 and 22.5 µm thickness, 300 folding endurance, 55.9 and 100% content uniformity, respectively. The Differential Scanning Calorimetry (DSC) showed no stable sample of sumatriptan and metoclopramide in the drug loaded films and revealed amorphous form and transition of hydrate to anhydrous form for metoclopramide. The results showed that the films prepared were fast dissolving. The films (sumatriptan combined with metoclopramide and sumatriptan alone) exhibited very good mucoadhesive properties and shorter retention time (15-30 s). Conclusion: The formulations were found to be suitable candidates for the development of sublingual films for therapeutic uses.